Growth performance and carcass characteristics in finishing feedlot heifers fed different levels of chromium-enriched live yeast or fed zilpaterol hydrochloride - Vald?z-Garc?a, Yissel S.; Aguilera-Soto, J. I.; Barreras, A.; Estrada-Angulo, A.; G?mez-Vazquez, A.; Plascencia, A.; Reyes, Julio J.; Stuart, Justiniano; Torrentera, Noem? G. (Cuban Journal of Agricultural Science, 2011)
Sixty crossbred heifers (371 ? 7 kg) were used in a 63-d feeding trial (4 pens per treatment in a randomized complete block design) to evaluate the influence of dietary supplementation with zilpaterol hydrochloride (?-agonist) or with different levels of chromium-enriched live yeast (Cr-YC) on growth performance and carcass characteristics. Heifers were fed a diet based on steam-flaked corn (1.45 Mcal of net energy of gain, NEg kg-1). Treatments were: 1) control, no yeast, no zilpaterol supplementation (Ctrl); treatments 2, 3 and 4) were the same basal diet supplemented with a commercial Cr-YC for a final dose of 10, 20 or 30 g hd-1 d-1 of yeast strain, and 5) the same basal diet (Ctrl) supplemented with 6 mg of zilpaterol kg-1 of feed for 30 d (ZIL), drug withdrawn from the diet 3 d pre-harvest. Compared with controls, ZIL increased final weight (3.8 %, P < 0.03), carcass-adjusted daily gain (18.7 %, P = 0.05), apparent dietary net energy of maintenance (14 %, P < 0.01), and decreased observed/expected DMI (14 %, P < 0.01). Treatment with ZIL did not affect (P < 0.13) marbling score, but, compared with control group, increased carcass dressing percentage (2.6 %, P = 0.01), and reduced (P = 0.02) kidney, pelvic and heart fat (KPH, 19.8 %) and fat thickness (9.4 %) and tended (5.9 %, P = 0.06) to increase Longissimus muscle area. Compared with Cr-YC treatments, ZIL increased apparent dietary NEm (P = 0.03) and dressing percentage (P < 0.01), and decreased observed/expected DMI (P = 0.03) and KPH (P=0.04). Treatment with Cr-YC did not affect carcass characteristics, but compared with control, Cr-YC supplementation tended to increase final BW (P = 0.08), ADG (0.09), fed:gain ratio (F:G, P = 0.08) and dietary NE (P = 0.06). Level of supplemental Cr-YC increased (linear component, P ? 0.04) final BW, ADG, F:G, apparent dietary NEm, and decreased (P = 0.02) observed/expected DMI. Level of supplemental Cr-YC did not affect (P ? 0.33) dressing percentage, LM area or marbling score, but, fat thickness and KPH decreased (P = 0.02) as Cr-YC level supplementation increase. DMI and HCW tended (P ? 0.08) to increase with increasing Cr-YC supplementation level. It is concluded that, zilpaterol supplementation increase growth performance in heifers as results of greater muscle accretion and for reduction of body fat. Chromium-enriched yeast supplementation increase growth performance and dietary NE, with modest effect in carcass characteristics. Better responses were observed at level of Cr-YC supplementation of 30 g hd-1 d-1 that corresponds to daily intakes of 1.65 ? 1011 colony forming units and 15 mg chromium. Key words: finishing cattle, ?-agonist, direct-fed microbials, feed efficiency, carcass traits.